2021
DOI: 10.1016/j.vaccine.2021.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine acceptability, uptake and completion amongst men who have sex with men: A systematic review, meta-analysis and theoretical framework

Abstract: Background: Due to an increased risk of sexually transmitted infections (STIs), gay, bisexual and other men who have sex with men (MSM) have been recommended to receive vaccinations against human papillomavirus, meningitis C and hepatitis A/B. This review aimed to compare the rates of vaccine acceptability, uptake and completion, and to identify determinants of vaccine outcomes specific to MSM to inform a theoretical framework.Methods: In January 2020 four databases were explored to identify vaccination behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 117 publications
5
47
0
Order By: Relevance
“…Provider recommendation is a major determinant of HPV vaccination among GBM and HPV vaccine acceptability is high among GBM and TW. 7 , 8 Major barriers are availability and convenience. 6 , 7 , 11 PrEP management visits are a potential venue for targeted HPV vaccine promotion.…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Provider recommendation is a major determinant of HPV vaccination among GBM and HPV vaccine acceptability is high among GBM and TW. 7 , 8 Major barriers are availability and convenience. 6 , 7 , 11 PrEP management visits are a potential venue for targeted HPV vaccine promotion.…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…Acceptability is high for HPV vaccination among GBM and TW. 7 , 8 Low uptake of HPV vaccination is likely a result of low awareness and missed opportunities during primary care. 9–11 Qualitative research has identified the need for alternative strategies for HPV vaccine delivery to increase convenience and availability for GBM and TW populations.…”
mentioning
confidence: 99%
“…Of the unvaccinated, only 40% heard about HPVV [19]. A meta-analysis in 2021 showed that the mean HPVV acceptability rate was 63%, uptake rate was 45% and completion rate was 47% among MSM of 78 studies, mostly performed in the United States [20]. Some of the reasons include the misconception about HPVV being reserved for women, the low perceived threat of HPV-related diseases and the stigma attached to HPVV [21].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the existing studies on HPV vaccine uptake in MSM do not report on an explicit theoretical approach or rely heavily on intrapersonal theories of health behavior (e.g., the theory of planned behavior) [ 13 ]. In the current study, Andersen’s model of healthcare utilization was used to identity predisposing (i.e., sociocultural factors that influence HPV vaccine decisions), enabling (i.e., factors that may facilitate utilization of HPV vaccination), and need based factors (i.e., professional judgment about an individual’s need for HPV vaccination) associated with HPV vaccination (initiation or intentions) among an at risk sample of Black and Hispanic MSM and gender-expansive young adults [ 14 ].…”
Section: Introductionmentioning
confidence: 99%